Clinical Characteristics of Colorectal Cancer Patients with Double Somatic Mismatch Repair Mutations Compared to Lynch Syndrome - Pearlman, Rachel (J Med Genet, 2019)
BACKGROUND: Colorectal cancer (CRC) patients with mismatch repair-deficient (dMMR) tumors without MLH1 methylation or germline MMR pathogenic variants (PVs) were previously thought to have Lynch syndrome (LS). It’s now appreciated that they can have double somatic (DS) MMR PVs. We explored clinical characteristics between patients with DS tumors and LS in two population-based cohorts. METHODS: We included CRC patients from Ohio 2013–2016 and Iceland 2000–2009. All had microsatellite instability testing and/or immunohistochemistry of MMR proteins, and MLH1 methylation testing when indicated. Germline next-generation sequencing was performed for all with dMMR tumors; tumor sequencing followed for patients with unexplained dMMR. Clinical characteristics of DS and LS patients were compared. RESULTS: Of the 232 and 51 patients with non-methylated dMMR tumors in the Ohio and Iceland cohorts, respectively, 57.8% (n=134) and 45.1% (n=23) had LS, 32.8% (n=76) and 31.4% (n=16) had DS PVs, 6% (n=14) and 9.8% (n=5) were unexplained, and 4.3% (n=10) and 13.7% (n=7) had incorrect IHC. Age of diagnosis for DS patients was older than LS patients (p=3.73×10(−4)) in the two cohorts. LS patients were more likely to meet Amsterdam II criteria (OR=15.81, p=8.47×10(−6)) and have multiple LS-associated tumors (OR=6.67, p=3.31×10(−5)). Absence of MLH1/PMS2 was predictive of DS PVs; isolated MSH6 and PMS2 absence was predictive of LS in both cohorts. CONCLUSIONS: Individuals with LS are 15x more likely to meet Amsterdam II criteria and >5x more likely to have multiple cancers as compared to those with DS tumors. Furthermore, isolated loss of MSH6 or PMS2 protein predicts LS.